4(4x+6)=3(2x+12)

Simple and best practice solution for 4(4x+6)=3(2x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(4x+6)=3(2x+12) equation:


Simplifying
4(4x + 6) = 3(2x + 12)

Reorder the terms:
4(6 + 4x) = 3(2x + 12)
(6 * 4 + 4x * 4) = 3(2x + 12)
(24 + 16x) = 3(2x + 12)

Reorder the terms:
24 + 16x = 3(12 + 2x)
24 + 16x = (12 * 3 + 2x * 3)
24 + 16x = (36 + 6x)

Solving
24 + 16x = 36 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
24 + 16x + -6x = 36 + 6x + -6x

Combine like terms: 16x + -6x = 10x
24 + 10x = 36 + 6x + -6x

Combine like terms: 6x + -6x = 0
24 + 10x = 36 + 0
24 + 10x = 36

Add '-24' to each side of the equation.
24 + -24 + 10x = 36 + -24

Combine like terms: 24 + -24 = 0
0 + 10x = 36 + -24
10x = 36 + -24

Combine like terms: 36 + -24 = 12
10x = 12

Divide each side by '10'.
x = 1.2

Simplifying
x = 1.2

See similar equations:

| t+2c= | | (2x^2)+7x-5=0 | | x+3x+1.5x=180 | | 7y=3x-23 | | (4-2x)=24 | | 5p^2-34+24= | | 8/9+i=0 | | g(x)=8 | | g(6)=8 | | 6y-12=5y-10 | | -3-(8x-4)=3(x+2)+7 | | -14x+7=21 | | -x-2(x+1)=1-7x | | 3(2x+8)=2(2x+40) | | 10x-7y=44 | | 5+2(x+3)=-x-6 | | 0=t^2+t-6 | | a+5=-16 | | -3(5+7p)=33-5p | | -2(x+7)=4x-7 | | -4=13.7 | | 15-3x=12-5x | | 4w(w-6)-2w^2=2w^2+8w-4 | | 2+3n=0.8n+18 | | 14-x=3x-2 | | x^3+5x^2+16x+80=0 | | 4/28=x/147 | | -7(x-6)-8=-5x+40 | | 5W+W=36 | | h=9(8m-9r) | | 6(-6-5)-6=0 | | ln(x+11)+ln(x-3)=2lnx |

Equations solver categories